What do we know about the future of pulses in global and regional agri-food systems? - Gbegbelegbe, Sika; Msukwa, Wupe; Nedumaran, Swamikannu; Alene, Arega D. (CGIAR, 2023)
Low and middle-income countries account for about 55% of global pulses production. Nearly half (48%) of global production occurs in 16 low- and lower-middle income countries in the drylands of South Asia and sub-Saharan Africa. The gap between pulse demand and supply is increasing in South Asia. Most recent foresight studies on pulses have focused on climate change impacts, adaptation, and mitigation. Future foresight studies on specific pulse crops should target regions where these pulses are important in human diets. Pulse trade should be promoted between countries which encompass the drylands of South Asia and sub-Saharan Africa.